Efeitos de diferentes inibidores da meiose sobre a maturação in vitro de oócitos bovinos e subsequente tolerância dos embriões a vitrificação - Maziero, Rosiára Rosária Dias [UNESP] (2014)
This work had as main objective to investigate the effect of BL-I and ROS in temporarily blocking the resumption of meiosis, acting on the factors that control the meiotic cell cycle of bovine oocytes and expansion of cumulus oophoros cells. In Experiment I, the oocytes remained in IVM mediafor 6, 12 and 24h in the presence of two concentrations of ROS (12.5 μM and 25 μM) or in the presence of BL-I (50 μ to 100 mM) or the association of ROS (6.25 μM) + BL-I (25 μM) and then cultured in a drug-free IVM media for 18, 12 or 24 h. After this time, the inhibited oocytes by 6 or 12 h were fertilized and cultured in vitro. Treatment with ROS and BL-I did not resulted in delay in germinal vesicle breakdown in relation to control. However, when used for 24 h, higher rates of oocyte degeneration were found. When these drugs were used for 12 h with reversion for more than 12 h, a lower blastocyst production rate compared to the control group was verified. However, after removal of the blockage for 6 h and maturation for 18 h, a higher number of oocytes treated with both ROS and BL-I were found in MII. Similarly, when the dose and duration of inhibition were reduced, the groups treated for 6 h of meiotic inhibition and reversion for 18 h showed similar embryo production rates to the control group. In Experiment II, oocytes remained in IVM mediafor 6 h in the presence of 12.5 μM of ROS or the presence of 50 μM of BL-I or the association of ROS (6.25 μM) + BL-I (25 μM) and then cultured in drug-free IVM media for 18 h. After this time, the inhibited oocytes were fertilized in vitro and the produced embryos were submitted to vitrification. The BI-I and ROS + BL-I groups showed superiority in embryo production, both in relation to the control as ROS group. The ROS + BL-I group showed higher rate of re-expansion after vitrification. Additionally, embryos from BL-I and BL-I + ROS showed lower number of apoptotic cells when compared to ...